2012
DOI: 10.3168/jds.2011-5233
|View full text |Cite
|
Sign up to set email alerts
|

Goat αs1-casein genotype affects milk fat globule physicochemical properties and the composition of the milk fat globule membrane

Abstract: Milk fat secretion is a complex process that initiates in the endoplasmic reticulum of the mammary epithelial cell by the budding of lipid droplets. Lipid droplets are finally released as fat globules in milk enveloped by the apical plasma membrane of the mammary epithelial cell. The milk fat globule membrane (MFGM) thus comprises membrane-specific proteins and polar lipids (glycerophospholipids and sphingolipids) surrounding a core of neutral lipids (mainly triacylglycerols and cholesterol esters). We have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 48 publications
3
20
1
Order By: Relevance
“…A higher mRNA abundance of MFGE8, a protein of the milk fat globule, observed in goats, together with the smaller average fat globule size (goats; 3.5 µm) in this species than in cows (4.0 µm; Park et al, 2007), could be related to previous results in different goat α S1 -CN genotypes showing a negative association between MFGE8 protein and milk fat globule size (Cebo et al, 2012). Moreover, the results of the study demonstrated significant correlations between most of the studied genes.…”
Section: Mammary Metabolismsupporting
confidence: 59%
“…A higher mRNA abundance of MFGE8, a protein of the milk fat globule, observed in goats, together with the smaller average fat globule size (goats; 3.5 µm) in this species than in cows (4.0 µm; Park et al, 2007), could be related to previous results in different goat α S1 -CN genotypes showing a negative association between MFGE8 protein and milk fat globule size (Cebo et al, 2012). Moreover, the results of the study demonstrated significant correlations between most of the studied genes.…”
Section: Mammary Metabolismsupporting
confidence: 59%
“…To assess the quality of individual MFGM samples, 25 mg of MFGM proteins were solubilized in the Laemmli buffer and resolved by 10 % SDS‐PAGE using the mini‐PROTEAN 3 electrophoresis module system (Bio‐Rad), followed by staining with Bio‐Safe (Bio‐Rad). MFGM samples displaying protein profiles consistent with previously reported ones were pooled for further studies (Fig. ).…”
Section: Methodsmentioning
confidence: 93%
“…Proteomic studies examining mammalian milk fat globules have identified caseins, indicating that these proteins are associated with milk lipids [100][102]. Specifically, casein modification alters lipid composition and protein components of the milk fat globule in goats [103]. The analogous functions of MGP2–10 and caseins suggest roles for these proteins as a source of amino acids, as stabilizers of milk homogeneity, and as carriers of polyatomic ions (i.e.…”
Section: Discussionmentioning
confidence: 99%